The importance of measuring prolactin prior to surgical management of a pituitary lesion: An illustrative case - Nikita Ollen-Bittle, MSc; Donald Lee, MD; Alain Proulx, MD, MSc; Neil Duggal, MD, MSc; Stan H.M. Van Uum, MD, PhD (Radiology Case Reports, 2023)
The characterization of sellar and suprasellar lesions is reliant on patient presentation, medical imaging, and hormone profiling. Prolactinomas are the most common type of functional pituitary adenomas, accounting for up to 57%. Importantly, prolactinomas can present without clear symptoms and with doubtful or even normal imaging. A 41-year-old male patient was referred to neurosurgery for consideration for resection of a sellar lesion, as initial CT imaging suggested a large meningioma. Subsequent MRI of the sella favored macroadenoma, meningioma, and craniopharyngioma as the top differential considerations. These conditions all indicate a diagnosis that would require surgical management. Clinical evaluation of this patient did not elicit any obvious clinical features suggestive of hyperprolactinemia. Fortunately, we obtained a full hormone panel which revealed a significantly elevated prolactin level of 17,390 µg/L. Based on this elevated prolactin level, we diagnosed a pituitary giant prolactinoma. Treatment with a dopamine agonist therapy was initiated and the response confirmed this diagnosis. This case demonstrates the importance of obtaining a prolactin level prior to surgical management of a sellar lesion. Had a prolactin level not been obtained, this patient would have undergone surgical resection based on both the imaging and clinical judgment.